A Welfare Analysis on Start-Up Decisions under Default Risk - Nicola Comincioli; Paolo Panteghini; Sergio Vergalli (Center for Economic Studies and ifo Institute (CESifo), 2021)
This short article studies the tax effects on a start-up investment decision under uncertainty. Since the representative firm can decide both when to invest and how much to borrow, the distortive effects are twofold. We thus show that the deadweight loss (namely, the ratio between the welfare loss and tax revenue) ranges from 25 to 32%, whereas mature firms face a lower distortion (as shown by Comincioli et al. (2021) the maximum deadweight loss is about 25%).
Keywords: H25; G33; G38; 330; real options; business taxation; default risk